Application Of Behavior Modification Using Flooding Techniques To Reduce Traumatic Children In PTSD - Ni Luh Putu Bagiartini; IGAA Noviekayatie (Proceedings of The ICECRS, 2020)
PTSD (Post Trauma Stress Disorder) is a maladigmatic reaction that can be experienced by an individual after experiencing a traumatic event in his life. This will have an adverse effect if the individual cannot eliminate the trauma, so that it can disrupt his daily activities. The main symptom of PTSD is involuntary backlash of traumatic events in the form of intrusive dreams or "shadows", which burst into consciousness suddenly (flashbacks). This research was conducted to reduce maladaptive behavior such as crying when listening to people talking loudly to children who see domestic violence in their parents. The subjects in this study were one person carried out for eighteen days divided into six days of assessment and twelve days of therapy. The method used in this research is behavior modification with flooding techniques, where the traumatic trigger stimulus will be presented directly to the subject and after that will be given an understanding of the situation. The results of research that have been done show that the subject is able to maintain the behavior of not crying when hearing a high tone of voice when hearing other people talk.